Draft genome sequences of enterohemorrhagic and enteropathogenic Escherichia coli strains isolated from alpacas in Peru - Maturrano L. (2018)
This study was supported by “Generación Científica-Becas Nacionales-Fortalecimiento de Programas de Doctorado en Universidades Peruanas” grant no. 215-2014-FONDECYT and by the Consejo Nacional de Ciencia y Tecnología (CONCYTEC).